Tax Revenue and Economic Growth in Developing Countries: A Narrative Synthesis of Empirical Evidence - Sekianti, Atik; Nuraini, Fariha (Sinergi International Journal of Economics, 2025)
This study explores the intricate relationship between tax revenue and economic growth in developing countries, aiming to evaluate how various tax structures influence economic outcomes. Employing a narrative review methodology, literature was sourced from databases such as Scopus and Google Scholar using a targeted set of keywords. Inclusion criteria focused on peer-reviewed empirical studies from the last two decades examining taxation, fiscal policy, and growth. Findings reveal that oil tax revenues can bolster short-term fiscal capacity but often introduce volatility tied to global price fluctuations. In contrast, non-oil taxes provide a more stable basis for sustained economic development. The review identifies a long-term correlation between tax revenue volatility and GDP instability, highlighting the critical role of institutional quality and administrative efficiency. Comparative studies show that G7 countries benefit from structured fiscal systems, while many developing countries struggle with inefficiencies, non-compliance, and narrow tax bases. Discussion points emphasize systemic barriers such as weak governance, informal economies, and low tax morale. Recommended reforms include administrative modernization, digitalization, and expanding the tax net to the informal sector. Ultimately, the study underscores that tax policy effectiveness hinges on contextual alignment with institutional capacities and socio-economic realities. Future research should address micro-level behaviors and long-term effects of taxation to enhance fiscal policy design.